Demineralization level of human tooth enamel after exposure to alcoholic and non-alcoholic beverages: A scanning electron microscopic study (Bangabandhu Sheikh Mujib Medical University Journal, 2024)
Background: In any beverage, human tooth enamel dissociates into its ionic products at a threshold pH of beverage